Ultrasound Doppler and tenosynovial fluid analysis in tenosynovitis. Issue 7 (25th March 2020) - Aslam, Fawad; England, Bryant R; Cannella, Amy; Sharp, Veronika; Kao, Lily; Arnason, Jon; Albayda, Jemima; Bakewell, Catherine; Sanghvi, Shruti; Fairchild, Robert; Torralba, Karina D; Evangelisto, Amy; et al.
Abstract : Objective: To assess Doppler ultrasound (US) and tenosynovial fluid (TSF) characteristics in tenosynovitis within common rheumatic conditions, as well as their diagnostic utility. Methods: Subjects with tenosynovitis underwent Doppler US and US-guided TSF aspiration for white cell count (WCC) and crystal analysis. Tenosynovial Doppler scores (DS) were semiquantitatively graded. TSF WCC and DS were compared using Kruskal-Wallis tests and logistic regression between non-inflammatory conditions (NIC), inflammatory conditions (IC) and crystal-related conditions (CRC). Receiver operating curves, sensitivity and specificity assessed the ability of WCC and DS to discriminate IC from NIC. Results: We analysed 100 subjects from 14 sites. The mean age was 62 years, 65% were female, and the mean TSF volume was 1.2 mL. Doppler signal was present in 93.7% of the IC group and was more frequent in IC than in NIC group (OR 6.82, 95% CI 1.41 to 32.97). The TSF median WCC per 10 9 /L was significantly higher in the IC (2.58, p<0.001) and CRC (1.07, p<0.01) groups versus the NIC group (0.38). A TSF cut-off of ≥0.67 WCC per 10 9 /L optimally discriminated IC versus NIC with a sensitivity and specificity each of 81.3%. In the IC group, 20 of 48 (41.7%) subjects had a TSF WCC <2.00 per 10 9 /L. Conclusions: A negative DS helps rule out IC in tenosynovitis, but a positive DS is non-specific and merits TSF testing. Unlike synovial fluid, a lower TSF WCC better discriminates IC from NIC. US guidance facilitates aspiration of minute TSF volume, which is critical for diagnosing tenosynovial CRC.